Analysis of factors influencing the parameters of electromagnetic environment. Issue 16 (19th December 2018) - Yu, Zhanqing; Wang, Xiaorui; Zeng, Rong; Fu, Yin; Liu, Lei; Li, Min
Abstract : Electromagnetic environment (EME) is one of the key issues during the ultra‐high voltage direct current power transmission projects. There are many factors affecting the parameters of the EME, which are mainly divided into line structure parameters and meteorological parameters. In this study, the concept of variable selection is used to analyse the influence of different factors on the EME parameters and to determine the factors which have greater influence. By comparing the advantages and disadvantages of the subset selection method and the compression estimation method, the more reliable results are determined. Then physical model and linear fitting method are used to analyse the influential factors of corona loss, audible noise, and radio interference.